Critical duration of grass weed interference in grain sorghum - Shaffer, Gared Eric (Kansas State University, 2016)
The availability of ALS-inhibitor herbicide-resistant grain sorghum hybrids will provide an opportunity to control grass weeds post-emergence with the ALS-inhibiting herbicide nicosulfuron (Zest[superscript]TM). More information on impact of grass weeds on sorghum yield are needed to optimize the application of nicosulfuron. The research objectives were to evaluate the impact of time of grass weed removal on grain sorghum yield when grown in different crop row spacing and seeding rates and to determine the critical duration of grass weed competition. Field studies were conducted in 2014 and 2015 at the KSU Agricultural Research Center at Hays, KS and the KSU Department of Agronomy Research Farm near Manhattan, KS. Four main treatments were grain sorghum row spacing of 25 and 76 cm at Hays or 20 and 76 cm at Manhattan, and two seeding rates of 125,000 and 150,000 seed ha⁻¹. Within each main plot, seven treatments were established including: weed-free all season using pre-emergence herbicides, weed-free all season by hand, weedy for 2, 3, 4, and 5 weeks after crop emergence in 2014 or weedy for 2, 4, 6, and 8 weeks after crop emergence in 2015, and weedy all season. The main grass weeds were giant, green, and yellow foxtail species, large crabgrass, and barnyardgrass. Grass weed biomass increased through the season at both locations in 2014 and in Manhattan in 2015. Hays 2014 grain sorghum aboveground stem and leaf biomass across row spacing and seeding rates decreased as weed removal time was delayed through the growing season. Grain sorghum yield decreased with increasing duration of grass weed competition in both years in Manhattan and in 2014 at Hays. Yield loss reached 5% at 2.3 to 25 weeks after sorghum emergence in narrow row spacing and 3.3 to 6.3 weeks after sorghum emergence in wide row spacing, depending on location, demonstrating that removing grass weed competition during these time frames will prevent more than 5% loss in grain sorghum yields.
Keywords: Grass Weed; Grain SorghumCritical Duration